Multidisciplinary Therapy in a Patient with Amelogenesis Imperfecta: A Case Report With 5-Year Follow-Up - ÖZTÜRK ÖZENER, HAFİZE (AVES PRESS LTD, 2017)
Amelogenesis imperfecta (AI) is a hereditary disorder that disrupts the formation of dental enamel in the primary and permanent dentition in the absence of systemic manifestations. The main concerns are caries susceptibility, poor esthetics, and generalized sensitivity. Treating these defects is not only important for esthetics and function but also for psychosocial health. Treatment planning for patients with AI is related to many factors: age and socioeconomic status of the patient, type and severity of the disorder, and the intraoral situation. In this case report, the 5-year results of a periodontal leveling process and fixed prosthetic restoration performed to regain esthetic and functional requirements in a female patient diagnosed with hypomature AI are presented.
Keywords: Amelogenesis imperfecta; dental esthetic; therapy; CLINICAL REPORT; CLASSIFICATION; REHABILITATION